Adrenomedullin mediates pro-angiogenic and pro-inflammatory cytokines in asthma and COPD. (June 2019) - Mandal, Jyotshna; Roth, Michael; Papakonstantinou, Eleni; Fang, Lei; Savic, Spasenija; Tamm, Michael; Stolz, Daiana
Abstract: Purpose: Adrenomedullin (AM) is a pluripotent peptide hormone with contradictory effects in human health and disease. In chronic inflammatory lung diseases, such as asthma and COPD, AM has been shown to inhibit inflammation and cell proliferation. In the present study, we aimed to investigate the effect of AM on pro-angiogenic and pro-inflammatory cytokines in asthma and COPD. Patients and methods: Serum levels of pro-AM were measured in patients with asthma, COPD and matched controls. The effect of AM on intracellular signaling proteins and cytokine secretion was assessed in primary cultures of epithelial cells (EC) and airway smooth muscle cells (ASMC) established from endo-bronchial biopsies of patients with asthma, COPD and controls. Results: Serum pro-AM was higher in patients with asthma and COPD, compared to controls. AM stimulated cAMP in ASMC but not in EC. In EC, AM decreased Erk1/2 MAPK expression and activation but in ASMC, AM activated Erk1/2. This effect was similar in asthma, COPD and controls. AM stimulated the secretion of pro-angiogenic CXCL1 by EC of controls and CXCL5 by EC of asthma patients. AM did not affect the secretion of IL-6 or IL-8 by EC but stimulated the secretion of IL-6 by ASMC. In EC, AM inhibited the stimulatory effect of TGF-β and IL-4 on the secretion of IL-6 and IL-8 but had an additive stimulatory effect with TGF-β in ASMC. Conclusions: These data suggest that AM mediates the secretion of pro-angiogenic and pro-inflammatory cytokines in a cell-type and/or a disease-specific way, explaining its association with clinical outcomes in COPD.